2020
DOI: 10.1007/s11606-020-06127-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Utilization of the Cerebrospinal Fluid Venereal Disease Research Laboratory Test for Diagnosis of Neurosyphilis: a Cohort Study

Abstract: BACKGROUND: Inappropriate use of diagnostic tests contributes to rising healthcare expenditures, and improving appropriate utilization rates is important for high-value patient care. The Venereal Disease Research Laboratory (VDRL) test performed in cerebrospinal fluid (CSF) has historically been improperly utilized, although there is no recent evaluation of its use in clinical practice. OBJECTIVES: Quantify the rates of appropriate CSF-VDRL testing, determine the CSF-VDRL false-positivity rate, and describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Antilipoidal antibodies are produced not only as a consequence of syphilis and other treponemal diseases but also in response to non-treponemal diseases of an acute and chronic nature in which tissue damage occurs ( 10 ). Although the incidence of biological false-positive VDRL tests is rare in spinal fluid samples ( 11 ), some studies have reported false-positive CSF VDRL results in the setting of central nervous system malignancy or HIV infection ( 12 14 ). However, for these syphilis patients, negative CSF-VDRL-10 results but positive CSF-VDRL-17 results may be indications for a very early phase of asymptomatic neurosyphilis and contribute to early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Antilipoidal antibodies are produced not only as a consequence of syphilis and other treponemal diseases but also in response to non-treponemal diseases of an acute and chronic nature in which tissue damage occurs ( 10 ). Although the incidence of biological false-positive VDRL tests is rare in spinal fluid samples ( 11 ), some studies have reported false-positive CSF VDRL results in the setting of central nervous system malignancy or HIV infection ( 12 14 ). However, for these syphilis patients, negative CSF-VDRL-10 results but positive CSF-VDRL-17 results may be indications for a very early phase of asymptomatic neurosyphilis and contribute to early diagnosis.…”
Section: Discussionmentioning
confidence: 99%